Penggunaan Media Balok terhadap Perkembangan Kognitif Anak Usia 4-5 Tahun di TK Al-Anwar Sumber Sari - Putriyatus Sani; Dewi Pusparini; Mediyana Mediyana (Universitas Palangka Raya, 2025)
This study aims to determine how the use of block media can affect the cognitive development of children aged 4-5 years at Al-Anwar Sumber Sari Kindergarten. The background of this study is based on the fact that most children in the school still have difficulty in recognizing shapes, colors, numbers, to arranging patterns and solving simple problems. Block media was chosen because it is considered capable of stimulating children's thinking power through fun and meaningful play activities. The method used in this study is descriptive qualitative, with data collection techniques in the form of observation, interviews, and documentation. The results of the study showed that block media had a significant impact on children's cognitive development. Children become more active, focused, and able to think more logically and systematically. In addition, through the activity of arranging and grouping blocks, children are also trained to work together and learn to solve problems creatively. Where the use of block media has proven effective in helping to improve children's cognitive aspects, especially in recognizing shapes, colors, numbers, and logical thinking skills. This media is also suitable for schools that have limited facilities, because it can be made simply and remains attractive to children.